Efektivitas Penilaian Proyek pada Mata Kuliah Teknik Listrik dan Elektronika Berbantuan Virtual Laboratory Tinkercad Terhadap Kreativitas Mahasiswa Pendidikan Teknik Mesin - Ridho Nurhuda; Muhammad Kholil (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to determine the effectiveness of the TinkerCAD virtual laboratory-assisted project assessment on Mechanical Engineering Education students at Sebelas Maret University of Surakarta who take the Electrical and Electronics Engineering course. The method used in this study is the one group pretest-posttest design method. The pre-test is used to determine the level of creativity of students before being given treatment. Pre-test and posttest creativity level data will be analyzed to determine their effectiveness. This study used paired t-test data analysis techniques and n-gain score tests. The results of the study show that the application of TinkerCAD's virtual laboratory-assisted project assessment can be said to be effective. This finding was supported by an increase in the average creativity score of 82.22%, from the initial test score of 47.08 to 85.79 in the final test.